Verification and Processing of Academic Certificates Using Web Services - Emeka, Anichebe Gregory (PERSPEKTIF, 2024)
A web service is a set of code of a server application that performs a specific task or service whenever it is invoked through a Remote Procedure Call (RPC) by a client application that is connected to the server over the Internet. Web services are one of the digital strategies that can be used by the government for curtailing academic certificate scandals being perpetrated by fraudulent individuals in various sectors of the economy. The traditional method of checking academic records and certificates manually is inefficient and prone to forgery by unscrupulous elements. Similarly, the e-transcript system being adopted by some organizations to authenticate the academic qualifications of individuals for possible admission or employment still involves a manual process. The objective of this work therefore is to show how web services for certificate verification of all tiers of the educational system in Nigeria can be maintained by one central body which is the Federal Ministry of Education in Nigeria to enable various end-users (such as educational institutions, commercial organizations, etc) use the web services to authenticate and process the academic records of individuals effortlessly. A simulated data of 20 SSCE results of students who completed their secondary school education at various institutions was used to illustrate the application of a web service. The web service program was written in Java. A client application which was also written in Java was used to query the web service through RPC to authenticate and process the certificate claims of a sample of five students for admission into a tertiary institution. Results showed that the web service excellently ascertained the eligible candidates for admission and those that were not. The web service technology is therefore highly recommended for use by the federal ministry of education in Nigeria to eradicate the academic certificate scandals amongst the citizenry.